Correcting the record of volcanic stratospheric aerosol impact: Nabro and Sarychev Peak. Issue 17 (3rd September 2014) - Fromm, M.; Kablick, G.; Nedoluha, G.; Carboni, E.; Grainger, R.; Campbell, J.; Lewis, J.
Abstract Since 2010, several papers have been published that reveal a pattern of discrepancies between stratospheric aerosol data from the Optical Spectrograph and Infrared Imaging System (OSIRIS) instrument and other measurements and model simulations of volcanic plumes from Kasatochi, Sarychev Peak, and Nabro volcanoes. OSIRIS measurements show two discrepancies, a posteruption lag in aerosol onset/increase and a low bias in maximum stratospheric aerosol optical depth. Assumed robustness of the OSIRIS data drove various conclusions, some controversial, such as the contention that the June 2011 Nabro plume was strictly tropospheric, and entered the stratosphere indirectly via the Asian monsoon. Those conclusions were driven by OSIRIS data and a Smithsonian Institution report of strictly tropospheric injection heights. We address the issue of Nabro's eruption chronology and injection height, and the reasons for the OSIRIS aerosol discrepancies. We lay out the time line of Nabro injection height with geostationary image data, and stratospheric plume evolution after eruption onset using retrievals of sulfur dioxide and sulfate aerosol. The observations show that Nabro injected sulfur directly to or above the tropopause upon the initial eruption on 12/13 June and again on 16 June 2011. Next, OSIRIS data are examined for nonvolcanic and volcanically perturbed conditions. In nonvolcanic conditions OSIRIS profiles systematically terminate 1–4 km above the tropopause. Additionally, OSIRIS profiles terminate when 750 nm aerosol extinction exceeds ∼0.0025 km−1, a level that is commonly exceeded after volcanic injections. Our findings largely resolve the discrepancies in published works involving OSIRIS aerosol data and offer a correction to the Nabro injection‐height and eruption chronology.